Strategi Pembelajaran Bahasa Arab secara Daring untuk Anak Usia Sekolah Dasar: Studi Kasus di Maha Arabic Center - Khayatul Khusna, Qothrunnida; Hafidah (Rayah Al-Islam, 2025)
The limited time allocated for Arabic language learning in elementary schools highlights the need for additional, flexible, and engaging classes. Maha Arabic center is an online learning platform specifically designed for children, using a visual, audio, and hands-on approach. This study aims to explain the learning strategies implemented in the Maha Arabic center program. The research employed a qualitative descriptive method using observation, documentation, and interviews with 15 first-grade students from class 1A, along with feedback from parents. The results show that the strategies used include vocabulary introduction through videos and Arabic songs, muḥāḍarah (speaking practice) with native speakers, as well as structured online assignments and evaluations. These strategies have proven effective in increasing children’s engagement, enthusiasm, and language skills. Moreover, parental involvement is also a crucial supporting factor in the learning process. Therefore, the Maha Arabic center learning strategy is relevant as an alternative model for online Arabic language learning for children.